2022
DOI: 10.17485/ijst/v15i22.164
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Application of Linear Programming on Product Mix for Profit Maximization and Cost Optimization

Abstract: Objectives: This research aims to sneak into the retailer's perception about that customer segment and plan a product mix accordingly. The focus is on small players in small towns not having deep pockets to synergize the product mix decisions effectively. Methods: The data used in this research paper is from Hatchers, a medium-sized enterprise with zero budget for software for product mix decisions. The data was collected through face-to-face interviews with ten representatives and five supervisors in complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Chanda et al [10] used linear programming to optimize the profit of a manufacturing sector using data obtained from market bread types. The research was able to identified pre-linear programming and post-linear programming application effect on product mix, with the findings that a higher profit was recorded, and that resources wastage and cost were at minimum level when linear programming was applied.…”
Section: Costmentioning
confidence: 99%
“…Chanda et al [10] used linear programming to optimize the profit of a manufacturing sector using data obtained from market bread types. The research was able to identified pre-linear programming and post-linear programming application effect on product mix, with the findings that a higher profit was recorded, and that resources wastage and cost were at minimum level when linear programming was applied.…”
Section: Costmentioning
confidence: 99%
“…The application of Linear Programming extends to the optimization of product mix, providing valuable insights into maximizing profit and minimizing costs for manufacturing companies (Hassan et al, 2020;Chanda et al, 2022). In mining engineering, it optimizes transportation, reducing costs and enhancing efficiency (Ali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Jaegler et al [41] presented a study that considers key questions regarding production control system implementation in a high product-mix and/or high routing-mix environment. Chanda et al [42] proposed a study that deals with the application of linear programming to product mix. According to de Jesus Pacheco [43], the operations plan must be integrated with corporate and business strategies in order to change and adhere to them.…”
mentioning
confidence: 99%